Inhibition and purification of acetylcholinesterases from adults and nymphs of Ricania simulans (Walker, 1851) (Hemiptera: Ricaniidae) - Dincer, Barbaros; Kizil, Demet (Springer Int Publ Ag, 2022)
Ricania simulans (Walker, 1851) (Hemiptera: Ricaniidae) has been causing damage in agricultural areas along the eastern Black Sea coastline since 2006. As there are not enough studies on managing this pest, it continues to pose a threat. One of the significant control tactics of insecticides includes the inhibition of acetylcholinesterase. Therefore the present study is aimed to study an alternative way to combat R. simulans through inhibition of acetylcholinesterase (ACHE). The ACHE was purified from adults and nymphs of R. simulans one by one using one-step edrophonium-Sepharose 6B affinity chromatography, and some kinetic properties were studied. The ACHEs were purified 251.6-fold with a yield of 34.2% for adults and 65.5-fold with a yield of 2.2% for nymphs. The K-m, V-max, and k(cat) values of R. simulans ACHE for acetylthiocholine iodide (ATC) hydrolysis were determined to be 0.04 +/- 0.01 mM, 2,000.0 +/- 250 EU/mg protein and 104.5 +/- 13 min(-1) for adults and 0.02 +/- 0.01 mM, 500.0 +/- 52 EU/mg protein and 30.3 +/- 6.4 min(-1) for nymphs, respectively. In inhibition studies of R. simulans ACHEs with edrophonium chloride, tacrine and olive leaf extract with water, the IC50 values of the inhibitors were calculated. Although all inhibitors inhibited the ACHEs, they inhibited the nymphs' ACHEs more effectively. In particular, the fact that the olive leaf water extract is effective in the ACHEs inhibition of these two stages is important for it to be an environmentally friendly pesticide that can be used in the fight against this pest.
Keywords: Acetylcholinesterase; Ricania simulans; Purification; Inhibition